Iot-Home Automation System (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2025)
People use the technology to make their everyday lives easy. They may need to communicate with their homes from anywhere in the world and at any time of the day. The most popular way is using their smart mobile phones to communicate with their homes. The most important thing in smart homes is the protection from disasters such as fire and gas leaking. In this thesis a smart home automatic protection system has been developed that is controlled by an application running on a mobile device. The developed mobile application can control and monitor the smart home via the Internet and using the SMS to send commands. With the help of the developed mobile application, the user can open/ close the doors, open / close the windows, open/ close any pump in the house, open / close any fans, open/close lights in the home, and also open/close the air-conditioning system, for example before coming home. The user can monitor the ambient temperature, humidity and most importantly the gas level at home. Then ovelties of the developed system are that the system can automatically control the firefighting and gas leaking. Additionally, one of the most important novelties of the developed mobile application is that the user can get feedback from the control actions to ensure that the required control actions have been implemented successfully.